Disease acceptance and social support in patients with peripheral vascular diseases treated in the surgical ward - Józefa Czarnecka PhD, RN, MSc; Ewa Kobos PhD, RN, MSc; Zofia Sienkiewicz PhD, RN, MSc (Wiley, 2021)
Abstract Aim The purpose of this study is a comparative analysis of the degree of disease acceptance and social support in patients with peripheral vascular diseases and other medical conditions treated in surgery ward. Design A cross‐sectional study. Methods This cross‐sectional study compares disease acceptance and social support in a group of 212 patients with peripheral vascular diseases and other conditions treated in surgery ward. A standardized Acceptance of Illness Scale (AIS) and Social Support Scale were used to collect the research data. Results Overall, on the AIS, 14% of patients with surgical diseases and 34% of patients with vascular diseases had a low disease acceptance rate. A high level of support was demonstrated in 41% of study participants with surgically treated diseases and in 17% of participants with vascular diseases.